Reduced calcification and osteogenic features in advanced atherosclerotic plaques of mice with macrophage-specific loss of TRPC3 - Dube, Prabhatchandra R. (2018)
Background and aims: Recent in vitro studies have showed that in macrophages, deletion of the non-selective Ca2+-permeable channel TRPC3 impairs expression of the osteogenic protein BMP-2. The pathophysiological relevance of this effect in atherosclerotic plaque calcification remains to be determined. Methods: We used Ldlr−/− mice with macrophage-specific loss of TRPC3 (MacTrpc3−/−/Ldlr−/−) to examine the effect of macrophage Trpc3 on plaque calcification and osteogenic features in advanced atherosclerosis. Results: After 25 weeks on high fat diet, aortic root plaques in MacTrpc3−/−/Ldlr−/− mice showed reduced size, lipid and macrophage content compared to controls. Plaque calcification was decreased in MacTrpc3−/−/Ldlr−/− mice, and this was accompanied by marked reduction in BMP-2, Runx-2 and phospho-SMAD1/5 contents within macrophage-rich areas. Expression of Bmp-2 and Runx-2 was also reduced in bone marrow-derived macrophages from MacTrpc3−/−/Ldlr−/− mice. Conclusions: These findings show that, in advanced atherosclerosis, selective deletion of TRPC3 in macrophages favors plaque regression and impairs the activity of a novel macrophage-associated, BMP-2-dependent mechanism of calcification.